Using Digital Pythagorean Tangram to Enhance Mathematical Justification Skills of Prospective Mathematics Teachers - Adhitya, Yusuf; Putri, Nurmala Setianing; Bustaren, Bill Chairy Rizki (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Mathematical justification is a crucial skill for mathematics teachers because it emphasizes proof and reasoning. This study examines how using the media “Digital Pythagorean Tangrams,” a manipulable, multimedia tool on Polypad, can improve prospective teachers' justification skills when proving the Pythagorean theorem. This research used a one-group pretest-posttest design where students were given a pre-test, then received an intervention using the media, and subsequently completed a post-test. The participants included 44 mathematics education students at a university in Bandung. Instruments comprised a mathematical justification test (pretest and posttest) and Digital Pythagorean Tangram media. Pretest and posttest data were analysed to obtain the N-gain score to estimate the effect size. The N-gain data were analysed using a one-sample t-test to check whether the improvement was statistically significant. The results revealed an average N-gain score of 0.42, which falls into the medium category, demonstrating a notable improvement in students' mathematical justification skills before and after using the digital tangram media. The One-Sample t-test also indicated a significance level below 0.05, confirming that the increase in students' mathematical justification ability is significant. Integrating digital manipulatives into proof-oriented instruction can meaningfully enhance prospective teachers’ justification skills and may serve as a practical pedagogical approach in mathematics teacher education.